2009
DOI: 10.1016/j.cellbi.2008.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 60 Hz electromagnetic fields on the activity of hsp70 promoter: An in vitro study

Abstract: We have evaluated the effect of 60 Hz sinusoidal magnetic fields (MF) at 8 and 8 microT on expression of the luciferase gene contained in a gene construct labelled as Electromagnetic Field-plasmid (pEMF). The vector included the hsp70 promotor containing the 3 nCTCTn sequences previously described for the induction of hsp70 expression by magnetic fields, as well as the reporter of the luciferase gene. We also replicated the study of Lin et al. [Lin H, Blank M, Rossol-Haseroth K, Goodman R. Regulating genes wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
1
11
0
1
Order By: Relevance
“…The design of the experiment allowed us to see the effect of 60 Hz EMF exposure at 80 mT on the expression of hsp70 promoter in quadriceps muscle of mice. We previously found activation of hsp70 promoter in cultured HeLa and BMK16 cell lines (Rodríguez-de la Fuente et al, 2009) and in INER-37 cells (Heredia-Rojas et al, 2010) after exposure to 60 Hz EMFs of similar characteristics to the fields used in the present study. The vector here, called pEMF, included the three nCTCTn sequences previously described for the induction of hsp70 expression by magnetic fields.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The design of the experiment allowed us to see the effect of 60 Hz EMF exposure at 80 mT on the expression of hsp70 promoter in quadriceps muscle of mice. We previously found activation of hsp70 promoter in cultured HeLa and BMK16 cell lines (Rodríguez-de la Fuente et al, 2009) and in INER-37 cells (Heredia-Rojas et al, 2010) after exposure to 60 Hz EMFs of similar characteristics to the fields used in the present study. The vector here, called pEMF, included the three nCTCTn sequences previously described for the induction of hsp70 expression by magnetic fields.…”
Section: Discussionsupporting
confidence: 77%
“…We have previously reported an increased luciferase gene expression in cultured HeLa and BMK16 cell lines transfected with hsp70 promoter, when cells were treated with 60 Hz sinusoidal EMFs at 8 and 80 mT (Rodríguez-de la Fuente et al, 2009). In subsequent work (Heredia-Rojas et al, 2010), we demonstrated the induction of hsp70 expression by EMFs of similar characteristics in the INER-37 cell line; however, magnetic field exposure had no effect on the RMA E7 cells.…”
Section: Introductionmentioning
confidence: 76%
“…An increased luciferase gene expression was observed in both cell types transfected with hsp70 promoter which, according to these workers, contains MF response elements (Rodríguez-de la Fuente et al 2009).…”
Section: Introductionmentioning
confidence: 90%
“…The first evidence of possible health risks connected to exposures to EMFs dates back to 1979, when reports on the possible pathological effects of the prolonged proximity to certain configurations of power lines [Wertheimer and Leeper, ] or exposure to radar‐emitted radiofrequencies [Robinette et al, ] were first published. As evidence started to accumulate, the idea, albeit controversial, that chronic exposure to EMFs could pose a threat to human health was developed [Budinger, ; Wertheimer and Leeper, ; Kavet and Banks, ; Brown and Chattopadhyay, ; Kavet, ; Tenforde, ; Habash et al, ; Bellieni et al, ; Rodríguez‐De la Fuente et al, ; Carpenter, ; Monazzam et al, ; Belyaev et al, ; Pall, , ; Lasalvia et al, ] to the point that 220 scientists from different countries in the world signed an international appeal to the United Nations and World Health Organization (WHO) in 2016 highlighting the need to raise awareness in the general public and in health operators about the risks associated with chronic exposure to EMFs [Hardell, ]. This necessity has also been acknowledged by WHO and several governments [Belyaev et al, ].…”
Section: Electromagnetic Field Effects On Cells and Tissuesmentioning
confidence: 99%